Inner Peace needs of male psychiatric patients in post-war Croatia are associated with their needs to clarify open issues in their life and their needs for forgiveness - Glavas, Andrijana; Büssing, Arndt; Baumann, Klaus (Frontiers in Public Health, 2023)
Background: More than 25 years after the end of the Balkan war, many people of the post-war population are still traumatized by the war events and have been treated for post-traumatic stress disorder or other psychiatric diagnoses. We were interested in their Inner Peace needs, how these relate to indicators of mental health, and to their needs to clarify open processes in their life and to forgive and be forgiven.Materials and Methods: In a cross-sectional survey with standardized questionnaires (i.e., SpNQ, PCL-M, HADS, BMLSS), 638 male patients who were treated in seven psychiatric centers in Croatia were enrolled. 68% were diagnosed with PTSD, and 32% with other psychiatric diagnoses. Most had actively participated in the Balkan war (79%), 60% for the whole war period.Results: Strong needs to "immerse into beauty of nature" were stated by 47%, to "dwell at a place of quietness and peace" by 66%, and to "find inner peace" by 57%. These Inner Peace needs were highest in men treated with PTSD diagnoses as compared to men with other psychiatric diagnoses, and slightly lower in men who were active during the whole war period as compared to shorter phases of war participation. Regression analyses with Inner Peace needs as a dependent variable revealed that Clarification/Forgiveness needs were the best predictor, with further influences of PTSD symptoms and life satisfaction, explaining altogether 49% of variance. Best predictors of their PTSD symptoms were life satisfaction perceived burden, depressive symptoms, Inner Peace needs, religious Trust, and duration of war participation, explaining 60% of variance Conclusions: In Croatian male war participants in clinical treatment decades after the war, Inner Peace needs indicate their ongoing intention to let go of their disturbing experiences and to find states of inner peace, particularly at specific places of quietness and peace. These needs can be considered as metaphor of longing for wholeness, integrity, and safety in contrast to the ongoing impact of unresolved issues. Thus, apart from psychotherapeutic treatment, sheltered places of nature, inspiration and reconciliation might be an element to improve the difficult situation of post-war victims still suffering from their experiences.